KEPEMIMPINAN KHARISMATIK - Shidqiyah Shidqiyah; Zahratun Naemah; Dedi Eko Riyadi HS (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2020)
Leadership is the existence of a process in leadership to exert social influence on other people, so that other people carry out a process as desired by the leader. The most important point in this case is that leaders can influence their subordinates to do what their leaders lead with full awareness. One of the interesting things that the charisma taik leadership has is that it has an ideological goal to realize a generally agreed vision and mission for the common good. He is also someone who is able to foster motivation that is aligned with the mission of the group. The presence of this charismatic leadership really gives new energy to anyone who is approached or sees it, if he speaks then the words that come out of his mouth will be a living solution for anyone who hears them, will make the listeners' emotions provoked to be persistent and enthusiastic in carrying out the leader's orders. This type of research is a type of qualitative research with a type of literature study or commonly referred to as library research. A literature study is a study that seeks the main source of information or main data from the literature or from books, journals that are relevant to the research to be carried out.